The Complete Sequence and Comparative Analysis of a Multidrug-Resistance and Virulence Multireplicon IncFII Plasmid pEC302/04 from an Extraintestinal Pathogenic Escherichia coli EC302/04 Indicate Extensive Diversity of IncFII Plasmids - Ho, Wing Sze; Yap, Kien-Pong; Yeo, Chew Chieng; Rajasekaram, Ganeswrie; Thong, Kwai Lin (Frontiers in Microbiology, 2016)
Extraintestinal pathogenic Escherichia coli (ExPEC) that causes extraintestinal infections often harbor plasmids encoding fitness traits such as resistance and virulence determinants that are of clinical importance. We determined the complete nucleotide sequence of plasmid pEC302/04 from a multidrug-resistant E. coli EC302/04 which was isolated from the tracheal aspirate of a patient in Malaysia. In addition, we also performed comparative sequence analyses of 18 related IncFIIA plasmids to determine the phylogenetic relationship and diversity of these plasmids. The 140,232 bp pEC302/04 is a multireplicon plasmid that bears three replication systems (FII, FIA and FIB) with subtype of F2:A1:B1. The plasmid is self-transmissible with a complete transfer region. pEC302/04 also carries antibiotic resistance genes such as blaTEM-1 and a class I integron containing sul1, cml and aadA resistance genes, conferring multidrug resistance (MDR) to its host, E. coli EC302/04. Besides, two iron acquisition systems (SitABCD and IutA-IucABCD) which are the conserved virulence determinants of ExPEC-colicin V or B and M (ColV/ColBM)-producing plasmids were identified in pEC302/04. Multiple toxin-antitoxin (TA)-based addiction systems (i.e., PemI/PemK, VagC/VagD, CcdA/CcdB, and Hok/Sok) and a plasmid partitioning system, ParAB and PsiAB, which are important for plasmid maintenance were also found. Comparative plasmid analysis revealed only one conserved gene, the repA1 as the core genome, showing that there is an extensive diversity among the IncFIIA plasmids. The phylogenetic relationship of 18 IncF plasmids based on the core regions revealed that ColV/ColBM-plasmids and non-ColV/ColBM plasmids were separated into two distinct groups. These plasmids, which carry highly diverse genetic contents, are also mosaic in nature. The atypical combination of genetic materials, i.e., the MDR- and ColV/ColBM-plasmid-virulence encoding regions in a single ExPEC plasmid is rare but of clinical importance. Such phenomenon is bothersome when the plasmids are transmissible, facilitating the spread of virulence and resistance plasmids among pathogenic bacteria. Notably, certain TA systems are more commonly found in particular ExPEC plasmid types, indicating the possible relationships between certain TA systems and ExPEC pathogenesis.